Respected Colleague and Notable Scholar of Mongolian Studies - Yu.Kuzmin (Journal of International Studies, 2024)
This commemoration honors Yuri Kuzmin, a distinguished Russian scholar of Mongolian studies, on the occasion of his 70th birthday. Kuzmin’s extensive contributions encompass the history of Mongolia, Russian-Mongolian relations, and the development of Mongolian studies in Siberia. His academic journey began with a focus on Eastern history at Irkutsk State University, followed by a dissertation on Mongolian history, and has led to a prolific career with over 500 publications. Mongolian studies thrive in Irkutsk, where Yuri Kuzmin lives and works. As a devoted friend to the people of Mongolia, he has become a central figure in advancing Mongolian studies. Known for his warm hospitality, Kuzmin graciously welcomes all who visit, embodying the gracious spirit of Mongolian culture. Kuzmin’s scholarship has significantly advanced the understanding of Mongolian history in Russia, Mongolia, and globally, making him a cherished friend and esteemed colleague within the field.Монгол судлалын эрхэм нөхөр - Ю.КузьминНэрт монголч эрдэмтний 70 насны ойд зориулав.